2010
DOI: 10.1002/pssb.201046454
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and morphological properties of the electrochemically prepared step bunched silicon (111) surface

Abstract: 8062 42434Topographical and electronic and properties of step bunched Si(111), prepared by electrochemical processing in alkaline solution, are analyzed. Tapping mode atomic force microscopy (TM AFM) analysis shows that one bunched step consists of about 15 atomic steps (each 0.314 nm in height) and that the (111) oriented terraces have widths that range from 150 to 250 nm. Scanning tunneling microscopy (STM) experiments show a corrugation of the (111) terraces with an rms roughness of 0.5-0.8 nm, correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In synchrotron radiation photoelectron spectroscopy (SRPES) it was shown that these surfaces are in an accumulation condition where the Fermi level is located only 0.06 eV below the conduction band edge whereas from the bulk doping, this energetic difference amounts to 0.26 eV [29]. In separate Kelvin probe AFM measurements, it has been found that the negative charge associated with the accumulation condition is located at the step edges of the nanostructure [35] as schematically indicated in Fig. 1.…”
Section: Nanostructured Semiconductor Surfacesmentioning
confidence: 96%
“…In synchrotron radiation photoelectron spectroscopy (SRPES) it was shown that these surfaces are in an accumulation condition where the Fermi level is located only 0.06 eV below the conduction band edge whereas from the bulk doping, this energetic difference amounts to 0.26 eV [29]. In separate Kelvin probe AFM measurements, it has been found that the negative charge associated with the accumulation condition is located at the step edges of the nanostructure [35] as schematically indicated in Fig. 1.…”
Section: Nanostructured Semiconductor Surfacesmentioning
confidence: 96%
“…Such work is in progress. SRPES valence band measurements show a shift of the Fermi level that can be due to degenerately doped n + Si or to the formation of an accumulation layer [14]. Kelvin probe force microscopy reveals the anisotropic lateral distribution of the electrostatic potential, thus providing sites with different charge [14].…”
Section: The Step-bunched Si Substratementioning
confidence: 97%
“…This modified surface is characterized by extended rather smooth terraces and steps that are between 5 and 15 atomic bilayers (BL) in height. It has been shown by synchrotron radiation photoelectron spectroscopy (SRPES) [12,13], and Kelvin probe microscopy (KPM) [14] that an n-Si surface is in an accumulation condition where a two dimensional electron system is formed on the surface. KPM data show that the electrostatic (or Galvani) potential near step-edges of the nanostructure surface decreases corresponding to a localized increase of negative electronic charge [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electrodeposition of Pt from PtCl 2À 6 complexes onto n-Si yielded different sizes for H-terminated (1 1 1) surfaces and for the step bunched Si surface where the major terraces are (1 1 1) oriented and the bunched steps are likely to show (1 1 0) orientation [19,20]. At step bunched surfaces, the Pt NPs had an average width of 30 nm and a height of 3 nm.…”
Section: Deposition Energetics For Photovoltaic and Photoelectrocatalmentioning
confidence: 98%